2008
DOI: 10.1017/s0022215108002089
|View full text |Cite
|
Sign up to set email alerts
|

Retained knife blades in the ear, nose and throat: three cases

Abstract: We propose that radiography be performed on all patients presenting with facial stab injuries which are anything more than superficial. We further suggest that the direct extraction of sharp objects through the pathway of insertion is safe if radiological studies show no risk of vascular injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
7
1
Order By: Relevance
“…Studies have shown patients who present at emergency departments across the globe with such pattern of retained craniofacial foreign objects tend to have a high level of alcohol consumption [1] , [15] though contrary to what was found in our case report where no history of alcohol consumption was reported but rather assaulted by thieves while selling items at his shop.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Studies have shown patients who present at emergency departments across the globe with such pattern of retained craniofacial foreign objects tend to have a high level of alcohol consumption [1] , [15] though contrary to what was found in our case report where no history of alcohol consumption was reported but rather assaulted by thieves while selling items at his shop.…”
Section: Discussioncontrasting
confidence: 98%
“…In cases of excessive arterial bleeding, angiography can help to identify a bleeding vessel that can then be managed by selective embolization or surgical ligation. If the path of the knife is clear of the skull base and major vessels, angiography is not mandatory as was found in this reported case, thus not necessitating angiography [1] , [6] , [8] , [10] , [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Imaging with CT scans are vital in assessment of the injury to determine the path of the wound, and to identify vascular injury [1,3,4,7]. There have been several reports where there was successful removal of the foreign body via the entrance wound [1,2,7].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging with CT scans are vital in assessment of the injury to determine the path of the wound, and to identify vascular injury [1,3,4,7]. There have been several reports where there was successful removal of the foreign body via the entrance wound [1,2,7]. This was only performed after careful dissection and identification of important structures, and after confirming the absence of significant vascular injury [2,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 While there are well-established guidelines on the management of PNI, the literature on the management of a retained knife in the neck is mostly anecdotal as very few centers have accumulated sufficient experience to formulate evidence-based management algorithms for this specific scenario. [6][7][8][9][10][11] Certain management principles are generally agreed upon by most authors. Uncontrolled extraction outside the operating room (OR) is strongly discouraged.…”
Section: Introductionmentioning
confidence: 99%